2022
DOI: 10.1002/poc.4463
|View full text |Cite
|
Sign up to set email alerts
|

Aromaticity and antiaromaticity in monoheterocyclic three‐membered rings: Application of natural bond orbital theory

Abstract: Using natural bond orbital theory, aromatic stabilization energies (NBO-ASEs) were calculated for neutral and cationic monoheterocyclic three-membered rings C 2 H 2 X(R) n (X = group 14-17 elements of rows 3-5; R = F, H or SiH 3 ;and n = 0-2). Generally, there was a decrease in the (anti)aromatic nature of the molecule moving down the group as either the stabilizing orbital overlap (aromaticity) or destabilizing orbital interactions (antiaromaticity) were reduced due to larger atoms inducing longer bonds. (Ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Apart from classical cyclopropenyl cation, a large number of heteroatom substituted three-membered aromatic heterocycles were reported, such as B 3 H 3 2À , Al 3 H 3 2À , Si 2 BH 3 , etc. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] The bonding and aromaticity of 3-membered heteroaromatic cycles involving group 14 elements were extensively studied by Frenking and co-workers. [16] A large number of theoretical studies suggest that the replacement of À CH fragment by heavier heteroatom hydride results in hydrogen bridged structure with lone pair on a heavier atom as the most stable structure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from classical cyclopropenyl cation, a large number of heteroatom substituted three-membered aromatic heterocycles were reported, such as B 3 H 3 2À , Al 3 H 3 2À , Si 2 BH 3 , etc. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] The bonding and aromaticity of 3-membered heteroaromatic cycles involving group 14 elements were extensively studied by Frenking and co-workers. [16] A large number of theoretical studies suggest that the replacement of À CH fragment by heavier heteroatom hydride results in hydrogen bridged structure with lone pair on a heavier atom as the most stable structure.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] There are many studies reported on neutral three-membered main group hydrides isoelectronic to cyclopropenyl cation. [1][2][3][4][11][12][13][14] The replacement of one of the + CH in classical cyclopropenyl cation by isoelectronic species main group fragments was well studied. The replacement by BH gives a neutral boron analogue of cyclopropenyl cation borirene, C 2 BH 3 (Scheme 1, II).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation